2006
DOI: 10.1107/s1600536806034763
|View full text |Cite
|
Sign up to set email alerts
|

3-Fluorophenylboronic acid

Abstract: Key indicatorsSingle-crystal X-ray study T = 294 K Mean (C-C) = 0.007 Å R factor = 0.084 wR factor = 0.189 Data-to-parameter ratio = 13.0For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 2 publications
6
24
0
Order By: Relevance
“…We used the crystal structure of structurally similar phenylboronic acid, 3-fluorophenylboronic acid and 4-bromophenylboronic acid [16,18,20], because of not available in the literature of the 3BrPBA molecule, till now. The geometric parameters are compared with these results [16,18,20].…”
Section: Geometrical Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the crystal structure of structurally similar phenylboronic acid, 3-fluorophenylboronic acid and 4-bromophenylboronic acid [16,18,20], because of not available in the literature of the 3BrPBA molecule, till now. The geometric parameters are compared with these results [16,18,20].…”
Section: Geometrical Structuresmentioning
confidence: 99%
“…Cyrań ski et al [17] analyzed the molecular structures of phenylboronic acid and its dimer using X-ray structural analysis and spectroscopic methods. The crystal structures of 3-fluorophenylboronic acid and 2,4-difluorophenylboronic acid were identified by Wu et al [18] and Rodriguez et al [19], respectively. Shimpi et al [20] reported the crystal structures of 4-chloro-and 4-bromophenylboronic acids and hydrates of 2-and 4-iodophenylboronic acid in two different forms, which were characterized by single-crystal X-ray diffraction methods.…”
Section: Introductionmentioning
confidence: 97%
“…Although the crystal structure of 2fpba has not been reported up till now, almost similar structure of the 3-fluorophenylboronic acid (3fpba) has been studied by x-ray diffraction. [23] All the geometrical parameters are optimized at the critical points and are reported in Table S2 (Supporting Information) together with conformations to compare with the x-ray data of the molecule of 3fpba. The 2fpba molecule has four possible conformations, all-trans, all-cis and mixed trans-cis relative to the B-C bond.…”
Section: Geometrical Structurementioning
confidence: 99%
“…The calculated ring -B(OH) 2 (C4-B11) bond length in 2fpba molecule is 1.573 A • (ct), 1.589 A • (cc), 1.568 A • (tt) and 1.576 A • (tc). These bond lengths were compared with B-C distances in similar molecular structures (values of 1.579, 1.562 and 1.533 A • for crystals of pentafluorophenylboronic acid, [25] 3-fluorophenylboronic acid [23] and 3-bromophenylboronic acid, [26] respectively).…”
Section: Geometrical Structurementioning
confidence: 99%
See 1 more Smart Citation